Investigating The Effect of Excellent Parenting Program on The Behavioral Problems of Hearing Impaired Children - Aghaziarati, Ali; Ashori, Mohammad; Norouzi, Ghasem; P. Hallahan, Daniel (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This research was aimed at the effect of excellent parenting program on the behavioral problems of hearing impaired children. Materials and Methods: The present research method was quasi-experimental with a pre-test, post-test and follow-up design. The statistical population includes all parents of 4-6-year-old hearing-impaired children in Tehran in 2022, which was selected by simple random method among deaf and hard-of-hearing centers and associations. The number of samples in this study was 30 parents who were randomly assigned to two groups of 15 people, test and control. The experimental group was trained in 13 sessions of 90 minutes, 3 sessions a week; while for the control group, no special action was taken. After the training course, the parents of both groups were subjected to a post-test. The follow-up phase was also implemented after 45 days. The tools used were the child's abilities and behavioral problems questionnaire (Goodman, 1997). Findings: Data analysis was carried out using analysis of variance with repeated measurements and the results showed that excellent parenting program had a significant effect on the behavioral problems of hearing impaired children (p<0.05). Conclusion: Based on the findings, it can be concluded that excellent parenting program leads to reduction of behavioral problems of hearing impaired children.